Simultaneous Removal of Microcystis aeruginosa and 2,4,6-Trichlorophenol by UV/Persulfate Process - Wang, Jingwen; Wan, Ying; Yue, Siyang; Ding, Jiaqi; Xie, Pengchao; Wang, Zongping (Frontiers in Chemistry, 2020)
UV/persulfate (UV/PS) could effectively degrade algal cells and micro-organic pollutants. This process was firstly applied to remove Microcystis aeruginosa (M. aeruginosa) and 2,4,6-trichlorophenol (TCP) simultaneously in bench scale. Algal cells can be efficiently removed after 120 min reaction accompanied with far quicker removal of the coexisted TCP, which could be totally removed within 5 min in the UV/PS process. Both SO4• and HO• were responsible for algal cells and TCP degradation, while SO4• and HO• separately dominated TCP degradation and algal cells removal. Apart from the role of radicals (SO4• and HO•) for algal cells and TCP degradation, UV also played roles to some extent. Increased PS dose (0  4.5 mM) or UV intensity (2.71  7.82 mW/cm2) could enhance the performance of the UV/PS process in both TCP and algae removal. Although some intracellular organic matters can be released to the outside of algal cells due to the cell lysis, they can be further degraded by UV/PS process, which was a little inhibited by the presence of TCP. This study suggested the good potential of UV/PS process in the simultaneous removal of algal cells and micro-organic pollutants.